2018
DOI: 10.4049/jimmunol.1800822
|View full text |Cite
|
Sign up to set email alerts
|

Targeted Diet Modification Reduces Multiple Sclerosis–like Disease in Adult Marmoset Monkeys from an Outbred Colony

Abstract: Experimental autoimmune encephalomyelitis (EAE) in common marmosets is a translationally relevant model of the chronic neurologic disease multiple sclerosis. Following the introduction of a new dietary supplement in our purpose-bred marmoset colony, the percentage of marmosets in which clinically evident EAE could be induced by sensitization against recombinant human myelin oligodendrocyte glycoprotein in IFA decreased from 100 to 65%. The reduced EAE susceptibility after the dietary change coincided with redu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
45
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 28 publications
(48 citation statements)
references
References 56 publications
3
45
0
Order By: Relevance
“…He proposed that health can be enhanced and aging postponed through manipulation of the gut microbiota with host-friendly bacteria present in fermented milk (Mackowiak, 2013). This is exactly what we found in the twin study (Kap et al, 2018a). We observed a positive effect of the YBS on the proportion of bifidobacteria in the marmoset stool.…”
Section: Targeted Dietary Intervention In the Marmoset Eae Model: Wassupporting
confidence: 87%
See 3 more Smart Citations
“…He proposed that health can be enhanced and aging postponed through manipulation of the gut microbiota with host-friendly bacteria present in fermented milk (Mackowiak, 2013). This is exactly what we found in the twin study (Kap et al, 2018a). We observed a positive effect of the YBS on the proportion of bifidobacteria in the marmoset stool.…”
Section: Targeted Dietary Intervention In the Marmoset Eae Model: Wassupporting
confidence: 87%
“…For the experiment, one sibling of each twin was reverted to the old water-based supplement (WBS), starting 8 weeks prior to EAE induction, while the other sibling remained on the new yogurt-based supplement (YBS). In brief, the EAE incidence in the old WBS and new YBS groups differed, albeit not significantly (8/8 in the old diet group, 6/8 in the new diet group) (Kap et al, 2018a). In addition, we observed a significant reduction of spinal cord demyelination, markedly altered expression of genes involved in apoptosis and myelination in the brain, a marked reduction of CalHV3 expression and alteration of cellular immune parameters, which in previous studies have been implicated in the EAE pathogenesis.…”
Section: Targeted Dietary Intervention In the Marmoset Eae Model: Wasmentioning
confidence: 87%
See 2 more Smart Citations
“…Recent attention to the variation in husbandry practices has underscored the relevance of such variation in research reproducibility. 8,9 Strikingly, one research group found a 25% reduction in clinically evident recombinant protein-induced experimental autoimmune encephalomyelitis (EAE) in common marmosets fed a yoghurt-based supplemental diet that differed from the standard colony enrichment; the primary diet for both groups was the same.…”
Section: Introductionmentioning
confidence: 99%